Survey on the causal consistency of data - Junfeng TIAN; Yanbiao WANG; Xinfeng HE; Juntao ZHANG; Wanhe YANG; Ya’nan PANG (Tongxin xuebao)
Causal consistency is one of the important projects to ensure data consistency in distributed storage.The current research focuses on causal consistency including optimization of clock method,design of the protocol and the optimization of operation transaction sequence.In the actual cloud environment,in addition to clock skew and query amplification,there are also insecure factors such as Trojans and untrusted third parties,which will destroy the causal consistency metadata stored by users,and the consistency of user’s operating results,even affect the availability of the storage environment.From the perspective of performance improvement and security in distributed storage,the clock synchronization,data replications,analysis and design of server protocol,related research progress of the serialization of operational affairs were introduced combined with consensus mechanisms such as blockchain.At the same time,their principlest,advantages,limitations,and different utilities in terms of security constraints were discussed,and then the future development trends and follow-up research directions were point out at last,which would provide a reference and help for the research in this field.